Characterization of adhesivity of organic enriched sea spray aerosols by atomic force microscopy. (1st February 2023) - Ono, Kohei; Iwata, Ayumi; Fukuma, Takeshi; Iwamoto, Yoko; Hamasaki, Koji; Matsuki, Atsushi
Abstract: Aerosol particles can trigger various environmental issues, not only when they are airborne but even after their deposition. For example, highly corrosive sea spray aerosols (SSA) can be deposited on surfaces and cause damage to steel- or concrete-based infrastructure, especially in coastal areas. However, the extent to which the adhesive behavior of SSA is affected by different degrees of organic mixing has not been sufficiently studied. The goal of this study was to evaluate the adhesion forces of both laboratory-generated and ambient SSA with a variety of organic contents on an individual particle basis using atomic force microscopy. Aerosols were also generated using a bulk sea foam sample collected from the coast of Noto Peninsula, Japan to simulate SSA enriched in a complex mixture of marine organics. The adhesion force of the sea foam particles was compared with that of two types of standard monosaccharides (glucose and fucose), artificial inorganic sea salt (ASS), glucose and ASS mixtures at different mass ratios, and ambient sea salt (SS) particles. Pure monosaccharide or its mixtures showed substantially larger adhesion forces than predominantly inorganic particles such as ASS and SS. In addition, it was found that a fraction of sea foam particles showed similarly large adhesion forces, suggesting that organic (e.g., monosaccharides)-enriched SSA can be considerably more adhesive than inorganic salts. Furthermore, a few but surprisingly adhesive particles were also identified among ambient aerosols. Therefore, it is necessary to consider the abundance of organics such as saccharides to correctly evaluate the adhesivity of SSA. Graphical abstract: Image 1 Highlights: Atomic force microscopy was used to evaluate the adhesion forces of the sea spray aerosols on an individual particle basis. Organic-rich particles have been shown to exhibit substantially larger adhesion forces than inorganic particles. The presence of such highly adhesive particles was confirmed in the ambient atmosphere.